Psychoacoustical equivalents of tuning curves as determined by the post-stimulatory masking technique - JAROSZEWSKI, Antoni; RAKOWSKI, Andrzej (Archives of Acoustics, 1976)
The method and results of measurements of psychoacoustical timing cur¬evs covering about 6500 individual judgements are described. Three experienced music students served as subjects in the experiment. The slopes of tuning curves obtained reach 1040 to 2200 dB/oct at the characteristic frequency 1 kHz. With reference to KIANG's [7], TONNDORF'S [16] and MOLLER's [10] data the importance of functions of the cochlear nucleus or the higher neurons in the perception of pitch is discussed.